USING MOVIE SEGMENTS AND SCRIPT IN TEACHING TENSES IN EFL CLASSROOM - May Triranto Maharini; Anita Sari (LPPM Universitas PGRI Jombang, 2025)
This study aims at exploring and proving whether using movie segments and movie script as a contextual approach in teaching simple present perfect tense is beneficial to improve students’ comprehension and identify how accurate students use both tenses after experiencing the learning process. The method used is an action research in teaching English grammar focusing on tense which is present perfect tense. It is expected that teaching them might be effective by approaching them to those tenses contextually. Movie segments with the script would be used. The main problems that are needed to investigate in this study is: 1 How effective are the movie segments and script used in the process of teaching the present perfect tense? Do learners perform the present perfect tense more accurately after they learn both tenses using movie segments and script? The result shows that students’ comprehension of present perfect improved and their use of both sentences is accurate after using this method in the learning process.